2021
DOI: 10.1017/s1368980021004262
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning algorithms for predicting undernutrition among under-five children in Ethiopia

Abstract: Objective: Child undernutrition is a global public health problem with serious implications. In this study, estimate predictive algorithms for the determinants of childhood stunting by using various machine learning (ML) algorithms. Design: This study draws on data from the Ethiopian Demographic and Health Survey of 2016. Five machine learning algorithms including eXtreme gradient boosting (xgbTree), k-nearest neighbors (K-NN), random forest (RF), neural network (NNet), and the generaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 48 publications
1
37
0
1
Order By: Relevance
“…Despite Random Forest and XG Boost performing better than the traditional logistic regression, logistic regression still retains interpretability as the main advantage it has over the other ML algorithm. Similar studies used ML algorithms to predict the nutritional status of children using demographic health survey data [ 18 , 19 , 20 , 32 ]. Our results are similar to the findings of [ 19 ], which implicate the RF algorithm to be a superior predictor of stunting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite Random Forest and XG Boost performing better than the traditional logistic regression, logistic regression still retains interpretability as the main advantage it has over the other ML algorithm. Similar studies used ML algorithms to predict the nutritional status of children using demographic health survey data [ 18 , 19 , 20 , 32 ]. Our results are similar to the findings of [ 19 ], which implicate the RF algorithm to be a superior predictor of stunting.…”
Section: Discussionmentioning
confidence: 99%
“…These methods have been applied in predicting malnutrition using different datasets [ 16 , 17 , 18 , 19 ]. Furthermore, machine learning methods have been shown to be superior to classical statistical methods when solving classification problems [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The authors however suggest that Anaemia and VAD are important public health problems among the tribal population of North-East India, despite their rich biodiversity. Bezboruah et al ( 2021 ) conducted a cross-sectional study of 104 HIV-positive children in one of the tertiary care centers in North-East India. According to their study, compared to the older age group preschool children had a higher prevalence of anaemia.…”
Section: Introductionmentioning
confidence: 99%
“…Stunting problems in the short and long term in the process of child development, such as the occurrence of decline in cognitive function and other dangerous diseases, stunting problems need to be a priority, especially in the field of health [6]. Malnutrition is a serious problem in the global community resulting in chronic disease and death [7]. Malnutrition affects decreased muscle function, immune disorders, and brain dysfunction and can cause disorders of nerve development [8].…”
Section: Introductionmentioning
confidence: 99%
“…This study showed that of 107 children who were followed up to 48 months of age, 51% experienced stunting height-for-age Z-score (HAZ<-2) at birth which increased to 54% at 48 months of age. Research by Bitew et al [7] use algorithms on machine learning to predict toddlers' malnutrition in Ethiopia. Descriptive results show that the xgbTree algorithm has better predictive capabilities than common linear mixed algorithms.…”
Section: Introductionmentioning
confidence: 99%